2014
DOI: 10.1063/1.4873701
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of plasma expansion and shockwave formation in femtosecond laser-ablated aluminum plumes in argon gas at atmospheric pressures

Abstract: Plasma expansion with shockwave formation during laser ablation of materials in a background gasses is a complex process. The spatial and temporal evolution of pressure, temperature, density, and velocity fields is needed for its complete understanding. We have studied the expansion of femtosecond (fs) laser-ablated aluminum (Al) plumes in Argon (Ar) gas at 0.5 and 1 atmosphere (atm). The expansion of the plume is investigated experimentally using shadowgraphy and fast-gated imaging. The computational fluid dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…32 At these pressure levels, the plume is found to be decelerated even at very earlier times of its evolution which leads to collisional excitation and confinement and eventually the plume length is limited to a few mm. By comparing spectrally integrated images with spectrally filtered images, it can be inferred that spectrally integrated images follow the features and trends of emission from Cu I and Zn I species.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…32 At these pressure levels, the plume is found to be decelerated even at very earlier times of its evolution which leads to collisional excitation and confinement and eventually the plume length is limited to a few mm. By comparing spectrally integrated images with spectrally filtered images, it can be inferred that spectrally integrated images follow the features and trends of emission from Cu I and Zn I species.…”
Section: Resultsmentioning
confidence: 92%
“…Recent CFD modeling results also confirmed that the oscillatory internal shock waves routinely seen in ns laser ablation plumes were absent in the case of fs LA plumes at atmospheric pressure levels. 32 ICCD images obtained at different pressure levels showed significant changes in the plume's morphology and hence the aspect ratios (Fig. 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Accurate numerical simulations of the process of shock wave propagation in gases were performed by Dors and Parigger [11] and successfully compared with high-speed, high-resolution shadowgraph techniques. Other important computational and experimental studies on laser-induced shock waves were performed by Harilal and coworkers [12][13][14], in the framework of extensive and articulated research devoted to the study of the expansion of the laser plume in different ambient gases and experimental configurations [15][16][17][18][19][20]. In a recent paper, Hermann et al [21] studied the evolution of the pressure in a steel plasma, acquiring its emission spectrum and successfully comparing the experimental data with the results of computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Once the ambient pressure increases, the plume evolution is determined by the interactions of the laser plasma and ambient gas [25].…”
Section: Dynamics Of Laser Ablation Plasma Assimilated As a Fractal Fmentioning
confidence: 99%